STUDY OF THE STRESS-DEFORMED STATE OF THE HIP JOINT MODEL IN CHILDREN IN THE CONDITIONS OF NORMAL AND DYSPLASION - Onischenko, О.V.; Korolkov, O.I.; Кsonz, І.V.; Karpinsky, M.Yu.; Yaresko, О.V. (World of Medicine and Biology, 2020)
The work presents a comparative study of the stress-deformed state of the normal hip joint elements in children and in the case of its dysplastic changes. To achieve this purpose, several mathematical models of the child's hip joint were built using the finite elements method. In the process of constructing the calculation model, the geometric model of the pelvis-thigh was taken as a basis, which is based on the method of creating a model of geometric sections obtained from tomographic images. As a result of the performed mathematical study, significant changes in the nature of the stress-deformed state in the dysplastic hip joint compared to the norm, which, in our opinion, may be one of the significant factors delaying the formation of the acetabulum and progression of the thigh subluxation, as well as initiate occurrence of femoral head cartilage and acetabulum degeneration areas. The obtained data should contribute to the definition and optimization of methods for additional mechanical stimulation of the hip joint components for its normal development during treatment.
Keywords: hip joint; dysplasia; child; biomechanics; acetabulum